2006
DOI: 10.1515/znb-2006-0616
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of a Monofunctionalized Phloroglucin-Derivative: A Precursor for Heterotrinuclear meta-Phenylene Bridged Complexes

Abstract: As part of our synthetic efforts for new triplesalen derivatives, we reacted 2,4,6-triacetyl-1,3,5-trihydroxybenzene (1) with excess Cu(ClO 4 ) 2 · 6H 2 O, imidazole, and ethylenediamine. However, not the triple ketimine derivative was formed but the mononuclear Cu II complex [LCu II (ImH)]ClO 4 · 0.5EtOH · 0.5H 2 O (HL = 6-(1-(2-aminoethylimino)ethyl)-2,4-diacetyl-1,3,5-trihydroxybenzene) with only one ketimine function. This complex forms a one-dimensional coordination polymer in the solid state through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This is an additional piece of evidence, that there must be some kind of driving force for the dimerization of two trinuclear triplesalen complexes as has already been observed in [(talen t-Bu 2 )Cu II 3 ] 15 and [(talen t-Bu 2 ){Fe III (MeOH)(H 2 O)} 3 ] 3+ . 30 We assume that close van der Waals contacts of the tert-butylbenzene subunits support energetically this dimerization to supramolecular aggregates. The formation of [Mn III 6 ] 3+ has to be considered for the synthesis of the heptanuclear complexes [Mn III 6 M] n+ , in which the product of the reaction of H 6 talen t-Bu 2 with Mn II acetate is treated with a hexacyanometallate.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is an additional piece of evidence, that there must be some kind of driving force for the dimerization of two trinuclear triplesalen complexes as has already been observed in [(talen t-Bu 2 )Cu II 3 ] 15 and [(talen t-Bu 2 ){Fe III (MeOH)(H 2 O)} 3 ] 3+ . 30 We assume that close van der Waals contacts of the tert-butylbenzene subunits support energetically this dimerization to supramolecular aggregates. The formation of [Mn III 6 ] 3+ has to be considered for the synthesis of the heptanuclear complexes [Mn III 6 M] n+ , in which the product of the reaction of H 6 talen t-Bu 2 with Mn II acetate is treated with a hexacyanometallate.…”
Section: Discussionmentioning
confidence: 92%
“…15 Also, two [(talen t-Bu 2 ){Fe III (MeOH)(H 2 O)} 3 ] 3+ units dimerize and encapsulate the uncommon [Cl ◊ ◊ ◊ H ◊ ◊ ◊ Cl]unit. 30 An advantage of the ligand folding in the trinuclear complexes [(talen t-Bu 2 ){M(solv) n } 3 ] m+ is the pre-organization of the three metal ions for coordination of three facial nitrogen atoms of a hexacyanometallate [M(CN) 6 ] n-. Thus, reaction of the molecular building block [(talen t-Bu 2 ){Mn III (solv) n } 3 ] 3+ -formed in situ by reaction of H 6 talen t-Bu2 with Mn II acetate-with [Cr(CN) 6 ] 3and [Fe(CN) 6 ] 3resulted in the formation of the heptanuclear complexes [{(talen t-Bu 2 )Mn III 3 } 2 {Cr III (CN) 6 }] 3+ ([Mn III 6 Cr III ] 3+ ) 31 and [{(talen t-Bu 2 )Mn III 3 } 2 {Fe III (CN) 6 }] 3+ ([Mn III 6 Fe III ] 3+ ), 32 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…124,125,127,129,130 We applied several of these methods for the synthesis of a triplesalen ligand and obtained various new compounds. 131 The successful synthesis of a triplesalen ligand is based on an observation of Elias and coworkers. 127 They reported that the sterically more crowded amine function of diamine I (Scheme 4) does not react with ketones to form ketimines, but only with aldehydes to form aldimines.…”
Section: Ligand Synthesismentioning
confidence: 99%